Integrating Sustainability Metrics into DevSecOps: A Risk-Based Framework for Green Software Development - Rath, Ashwini Kumar (Digital Repository of Theses, 2025)
Software development and IT operations often contribute to environmental impact in ways that are frequently overlooked. As industries move toward sustainability, integrating green computing into DevSecOps workflows becomes essential. However, existing approaches lack structured methods to measure and mitigate environmental effects within software development, deployment, and management. This study introduces two structured frameworks that embed sustainability metrics and risk evaluation within DevSecOps, helping organizations lower energy consumption, improve resource efficiency, and maintain security without compromising agility. A mixed-methods research design was employed, incorporating both qualitative interviews and quantitative surveys to identify and assess sustainability indicators in DevSecOps adoption. The findings indicate a widespread awareness of green computing, yet a lack of standardized methodologies across software firms, including developer organizations and system integrators. By addressing this gap, the study provides actionable strategies for embedding sustainability into continuous integration, testing, and deployment processes. By bridging theoretical research with industry applications, this work equips organizations with measurable tools to align software engineering practices with sustainability goals. Ultimately, it advances academic discourse while offering practical insights for companies integrating environmental responsibility into DevSecOps. Keywords: DevSecOps, Green Computing, Sustainability, Software Development, Environmental Metrics, Framework Integration